2022
DOI: 10.48550/arxiv.2201.12108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dust entrainment in photoevaporative winds: Synthetic observations of transition disks

R. Franz,
G. Picogna,
B. Ercolano
et al.

Abstract: Context. X-ray-and extreme-ultraviolet-(XEUV-) driven photoevaporative winds acting on protoplanetary disks around young T-Tauri stars may strongly impact disk evolution, affecting both gas and dust distributions. Small dust grains in the disk are entrained in the outflow and may produce a detectable signal. In this work, we investigate the possibility of detecting dusty outflows from transition disks with an inner cavity. Aims. We compute dust densities for the wind regions of XEUV-irradiated transition disks… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…While the analytical work of Facchini et al (2016) sheds some light on these questions, it would be highly useful to run numerical simulations of multidimensional disks subject to external photoevaporation including embedded dust particles, similar to the works of Hutchison et al (2016), Franz et al (2020), and Franz et al (2022a, which address pure internal evaporation. For internal photoevaporation, Franz et al (2022b) found potentially observable cone or chimney-like features, which are more pronounced if the dust is considered as settled. Thus, observations in scattered and polarized light will also help to answer those questions.…”
Section: Dust Feedback On Photoevaporationmentioning
confidence: 97%
“…While the analytical work of Facchini et al (2016) sheds some light on these questions, it would be highly useful to run numerical simulations of multidimensional disks subject to external photoevaporation including embedded dust particles, similar to the works of Hutchison et al (2016), Franz et al (2020), and Franz et al (2022a, which address pure internal evaporation. For internal photoevaporation, Franz et al (2022b) found potentially observable cone or chimney-like features, which are more pronounced if the dust is considered as settled. Thus, observations in scattered and polarized light will also help to answer those questions.…”
Section: Dust Feedback On Photoevaporationmentioning
confidence: 97%